Anti-Tumor Effects of the Methanol Extract of Ecballium elaterium (L.) A. Rich Fruits on Human Gastric (MKN-45) and Breast (MCF-7) Cancer Cell Lines - Samaneh Keshavarz; Fatemeh Yousefbeyk; Saghi Jani Kargar Moghaddam; Mahsa Ramezanpour; Puyan Daei; Saeed Ghasemi; Masoud Hamidi; Javad Khalili Fard (Lorestan University of Medical Sciences, 2023)
Background and Aim: The Ecballium elaterium (L.) A. Rich belongs to the Cucurbitaceae family and is a Mediterranean medicinal herb with a medicinal background. In the present study, following our previous research, we aimed to evaluate the expression profile of certain significant genes involved in the process of apoptosis in human gastric (MKN-45) and breast (MCF-7) cancer cell lines treated with the methanol extract of E. elaterium fruits. Materials and Methods: The real-time PCR method was employed to calculate the expression levels of p53, bax, and bcl-2 genes in both MKN-45 and MCF-7 cell lines. Moreover, the bax/bcl-2 mRNA ratio was calculated in both cell lines. Results: Real-time PCR revealed that E. elaterium fruit extract-treated MKN-45 cells underwent a strong reduction in the mRNA levels of bcl-2 (0.04-fold) (p < 0.0001) together with an increase in p53 (18.23-fold) (p < 0.0001) and a significant reduction in bax (0.31-fold) (p <0.01). However, the up-regulation of bax (55.51-fold) (p< 0.0001) and bcl-2 (17.68-fold) (p< 0.05) genes with a concomitant revealed no significant result for p53 (2.32-fold) gene observed in MCF-7 cells. This extract had strong apoptotic activity on MKN-45 cells. The bax/bcl-2 mRNA ratio in E. elaterium fruit extract-treated MKN-45 cells was significant in comparison with the control group (7.24-fold higher and p= 0.0133), but this ratio was not remarkable in E. elaterium fruit extract-treated MCF-7 cells compared with the control group (3.95-fold higher and p= 0.0811). Conclusion: The results of this research indicated that E. elaterium fruit extract could be a promising therapeutic option against gastric cancer.